A New Score to Assess the Perioperative Period of the Cancer Patient Undergoing Non-Palliative Elective Surgery: A Retrospective Evaluation of a Case Report by PERIDIA Score - Andresciani, Letizia; Calabrò, Concetta; Laforgia, Mariarita; Ronchi, Maria; De Summa, Simona; Cariddi, Christel; Boccuzzi, Rosa; De Rosa, Anna; Rizzo, Elisabetta; Losito, Giulia; Bradascio, Grazia; Napoli, Gaetano; et al. (Frontiers in Oncology, 2021)
The complexity of cancer patients and the use of advanced and demolitive surgical techniques frequently need post-operatory ICU hospitalization. To increase safety and to select the best medical strategies for patient, a multidisciplinary team has performed a new peri-operatory assessment, arising from evidence-based literature data. Verifying that most of the cancer patients, admitted to the intensive care unit, undergo major surgery with localizations in the supramesocolic thoraco-abdominal area, the team focused the attention on supramesocolic peridiaphragmatic cancer surgery. Some scores already in use in clinical practice were selected for the peri-operatory evaluation process. None of them evaluate parameters relating to the entire peri-operative period. In detail, only a few study models were found that concern the assessment of the intra-operative period. Therefore, we wanted to see if using a mix of validated scores, it was possible to build a single evaluation score (named PERIDIAphragmatic surgery score or PERIDIA-score) for the entire peri-operative period that could be obtained at the end of the patient's hospitalization period in post-operative ICU. The main property sought with the creation of the PERIDIA-score is the proportionality between the score and the incidence of injuries, deaths and the length of stay in the ward. This property could organize a tailor-made therapeutic path for the patient based on pre-rehabilitation, physiotherapy, activation of social assistance services, targeted counseling, collaborations with the continuity of care network. Furthermore, if the pre-operative score is particularly high, it could suggest different or less invasive therapeutic options and if the intra-operative score is particularly high, it could suggest a prolongation of hospitalization in ICU. The retrospective prospective study conducted on 83 patients is still ongoing. The first data would seem to prove an increase of clinical complications in patients who were assigned a one third score with respect to the maximum (16/48) of PERIDIA-score. Moreover, patients with a 10/16 score within each phase of the evaluation (pre, peri and post), more frequently develop injuries. In the light of these evidence, the 29 point-score assigned to our patient can be considered as predictive for the subsequent critical and fatal complications the patient faced up.